Uptake of and willingness to pay for health insurance in rural Senegal: a reinforcement effect - Sylvie Boyer; Cheikh Sokhna; Bruno Ventelou; Marwân-al-Qays Bousmah (BMJ Public Health)
Introduction Expanding health insurance is viewed as a core strategy for achieving universal health coverage. In Senegal, as in many other developing countries, this strategy has been implemented by creating community-based health insurance (CBHI) schemes with voluntary enrolment and a fixed premium paid by enrollees. Yet little is known about how the individuals’ experience of CBHI enrolment further influences their willingness to pay (WTP). In this paper, we test the existence of a reinforcement effect between effective enrolment in a CBHI and WTP for health insurance by analysing their mutual relationship.Methods We rely on primary survey data collected in 2019–2020 in the rural area of Niakhar in Senegal. We use an econometric methodology involving: (1) Heckman-type selection models to estimate the determinants of CBHI membership conditioned on awareness of health insurance, addressing the issue of sample selection due to differential awareness and (2) a simultaneous equation model to jointly estimate the uptake and WTP for health insurance, addressing the issue of endogeneity due to reverse causality between both variables. We also focus on the roles that informational and geographical barriers, as well as individual risk preference and trust, play in both outcomes.Results The final sample includes 1607 individuals. Results show that WTP further increases with the individuals’ direct experience in a CBHI scheme, despite an environment characterised by low enrolment rates. We also provide evidence for a U‐shaped relationship between risk tolerance and WTP for health insurance.Conclusion We provide novel evidence on a reinforcement effect of enrolment in a CBHI on WTP for health insurance, with the presence of a substantial consumer surplus among enrolled individuals at the actual premium. Our findings suggest that policies aiming at improving health insurance awareness should foster the demand for health insurance in rural Senegal.